Respuesta :

[tex]log _{2x+7} 27 = 3 [/tex]
( 2 x + 7 )³ = 27
( 2 x + 7 )³ = 3³
2 x + 7 = 3
2 x = 3 - 7
2 x = - 4
x = ( - 4 ) : 2
x = - 2

Answer:

The solution of [tex]log_{2x+7}27\:=\:3[/tex] is -2.

Step-by-step explanation:

 Given : [tex]log_{2x+7}27\:=\:3[/tex]

We have to solve for x.

Consider the given expression [tex]log_{2x+7}27\:=\:3[/tex]

Apply rule, [tex]\log _a\left(b\right)=\frac{\ln \left(b\right)}{\ln \left(a\right)}[/tex]

[tex]\log _{2x+7}\left(27\right)=\frac{\ln \left(27\right)}{\ln \left(2x+7\right)}[/tex]

On  simplifying, we get,

[tex]\frac{\ln \left(27\right)}{\ln \left(2x+7\right)}=3[/tex]

Multiply both side by [tex]\ln \left(2x+7\right)[/tex]

We have,

[tex]\frac{\ln \left(27\right)}{\ln \left(2x+7\right)}\ln \left(2x+7\right)=3\ln \left(2x+7\right)[/tex]

Multiply fractions as [tex]\:a\cdot \frac{b}{c}=\frac{a\:\cdot \:b}{c}[/tex]

we get,

[tex]=\frac{\ln \left(27\right)\ln \left(2x+7\right)}{\ln \left(2x+7\right)}==\ln \left(27\right)[/tex]

Thus, becomes [tex]\ln \left(27\right)=3\ln \left(2x+7\right)[/tex]

Divide both sides by 3, we have,

[tex]\frac{3\ln \left(2x+7\right)}{3}=\frac{\ln \left(27\right)}{3}[/tex]

Apply rule [tex]\log _a\left(x^b\right)=b\cdot \log _a\left(x\right)[/tex]

[tex]\ln(27)=\ln \left(3^3\right)=3\ln \left(3\right)[/tex]

Thus, [tex]\ln \left(2x+7\right)=\ln \left(3\right)[/tex]

[tex]\mathrm{When\:the\:logs\:have\:the\:same\:base:\:\:}\log _b\left(f\left(x\right)\right)=\log _b\left(g\left(x\right)\right)\quad \Rightarrow \quad f\left(x\right)=g\left(x\right)[/tex]

2x+ 7 = 3

Subtract 7 both sides, we get,

2x = 3 - 7

Simplify , we have,

2x = -4

Divide both side by 2, we have

x = -2

Thus, the solution of [tex]log_{2x+7}27\:=\:3[/tex] is -2.